The occurrence and biogeochemical cycling of quaternary, ternary and volatile amines in marine systems - Fitzsimons, Mark F.; Airs, Ruth; Chen, Yin (Frontiers in Marine Science, 2024)
This review provides a critical assessment of knowledge regarding the occurrence and behaviour of volatile, low molecular weight amines, particularly methylamines and quaternary amines, in marine aquatic systems. It provides an up-to-date evaluation of their presence within marine ecosystems, the processes likely to control their flux across the sea-air interface, and analytical techniques associated with their measurement. Interest in the occurrence and cycling of these groups of compounds in seawater has increased within the last 10–15 years, due to their potential role in climate regulation. As such, the need for wider measurements and mechanistic studies to elucidate their role within biological communities and, more widely, the nitrogen cycle and marine ecosystem models, is apparent. Finally, we make recommendations on what research questions are most suitable for future studies in this area.